(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Indian government focused on education in its national policy which reflected upon the university education commission 1948 under the chairmanship of Dr. Radha Krishnan. It contained the aim and functions of higher education which provides people with opportunities to reflect on the critical social, economic, cultural, moral and spiritual issues relating to humanity. It contributed towards national development through dissemination of specialized knowledge and skills which ensured a critical factor for survival. Being the apex of the educational pyramid, knowledge and skills have a key role in producing both teachers and students with quality in the educational system. Developments in the Indian economy brought about advancements in education while coping with technology changes in the current scenario of the nation. The quality of the education system had to undergo many transformations in technology on education which could bring about professional development in both students and teachers concerned. Education provides a way of life. It is related to 7R’s i.e., reading, writing, arithmetic, rights, responsibility and their relationship and recreation. Lack of human qualities prevail with any person who possesses high literacy with sound degrees may be coined as educated. Education is concerned with the development of character and personality of an individual that may affect one’s personal development. Educational institutions may be a miniature in society but they are recognized as the mirror of society. Teachers who are the link between education and the student thereby fetch in the development toward democratic citizenship, personality, art of living, professional skills, leadership and devotion to the country, if the linking system fails it affects the society.